LOKALISASI PLAT NOMOR DENGAN JAVA MENGGUNAKAN DETEKSI TEPI CANNY DAN FILTER MORFOLOGI - Ulmiah Muis; Yaumil Afwan; Zahir Muhammad Adin (Universitas Negeri Makassar, 2023)
This study aims to introduce an automatic vehicle identification system based on vehicle licenses and license plate recognition. This Automatic Number Plate Recognition (ANPR) system software uses a series of image processing algorithms captured by a camera with a high degree of accuracy and has the efficiency to recognize license plates and then identify vehicles from datasets stored on a Personal Computer (PC). This study uses an algorithm for license plate localization by implementing the Canny edge detection algorithm and a morphological filter.The methodology used is to develop a Number Plate (NP) localization method including the following steps: (1) Color conversion, image enhancement (using sharpness filters and gamma correction), Canny edge detection and alignment (skeletonization); stage (2) morphological filter-based method to determine the Region of Interest (ROI), namely a rectangular box containing a Number Plate (NP). A rectangular bounding box is drawn across the area in the original image that contains the NP after the NP are localized. The bounding box is equal to the width of the image plus one pixel and the height of the NP plus one pixel.The results showed that this method succeeded in achieving a localization rate of about 72.0%. The method used for license plate localization is able to localize license plates with clear boundaries and unambiguous separation of other related components. This research can be further developed to include more functions so that it can be used by all elements of society from researchers to law enforcers.